Harms, benefits, and the nature of interventions in pragmatic clinical trials. (October 2015) - Ali, Joseph; Andrews, Joseph E; Somkin, Carol P; Rabinovich, C Egla
To produce evidence capable of informing healthcare decision making at all critical levels, pragmatic clinical trials are diverse both in terms of the type of intervention (medical, behavioral, and/or technological) and the target of intervention (patients, clinicians, and/or healthcare system processes). Patients and clinicians may be called on to participate as designers, investigators, intermediaries, or subjects of pragmatic clinical trials. Other members of the healthcare team, as well as the healthcare system itself, also may be affected directly or indirectly before, during, or after study implementation. This diversity in the types and targets of pragmatic clinical trial interventions has brought into focus the need to consider whether existing ethics and regulatory principles, policies, and procedures are appropriate for pragmatic clinical trials. Specifically, further examination is needed to identify how the types and targets of pragmatic clinical trial interventions may influence the assessment of net potential risk, understood as the balance of potential harms and benefits. In this article, we build on scholarship seeking to align ethics and regulatory requirements with potential research risks and propose an approach to the assessment of net risks that is sensitive to the diverse nature of pragmatic clinical trial interventions. We clarify the potential harms, burdens, benefits, and advantages of common types of pragmatic clinical trial interventions and discuss implications for patients, clinicians, and healthcare systems.